Hepatitis C Testing, Status and Treatment among Marginalized People Who Use Drugs in an Inner City Setting: An Observational Cohort Study. (2nd January 2019) - Boucher, Lisa M.; Bayoumi, Ahmed M.; Mark, Amy E.; Cooper, Curtis; Martin, Alana; Marshall, Zack; Boyd, Rob; Oickle, Pam; Diliso, Nicola; Pineau, Dave; Renaud, Brad; LeBlanc, Sean; et al.
ABSTRACT: Background: Chronic hepatitis C virus (HCV) infection is common among people who inject drugs (PWID) and is associated with morbidity and premature death. Although HCV can be cured, treatment may be inaccessible. We studied HCV testing, status and treatment among marginalized people who use drugs in Ottawa, Canada, a setting with universal insurance coverage for physician services. Methods: We analyzed data from the Participatory Research in Ottawa: Understanding Drugs study, a cross-sectional, peer-administered survey of people who use drugs from 2012 to 2013. We linked responses to population-based health administrative databases and used multivariable Poisson regression to identify factors independently associated with self-reported HCV testing, self-reported positive HCV status, and database-determined engagement in HCV treatment. Results: Among 663 participants, 562 (84.8%) reported testing for HCV and 258 (45.9%) reported HCV-positive status. In multivariable analysis, HCV-positive status was associated with female gender (RR 1.27; 95%CI 1.04 to 1.55), advancing age (RR 1.03/year; 95%CI 1.02 to 1.04), receiving disability payments (RR 1.42; 95%CI 1.06 to 1.91), injecting drugs (RR 5.11; 95%CI 2.64 to 9.91), ever injecting with a used needle (RR 1.30; 95%CI 1.12 to 1.52), and ever having taken methadone (RR 1.26; 95%CI 1.05 to 1.52). Of HCV positive participants, 196 (76%) were engaged in primary care but only 23 (8.9%) had received HCV therapy. Conclusions/Importance: Although HCV testing and positive status rates are high among PWID in our study, few have received HCV treatment. Innovative initiatives to increase access to HCV treatment for PWID are urgently needed.